КОМУТАЦІЙНІ ПЕРЕНАПРУГИ У ТРАНСФОРМАТОРАХ НАПРУГИ - Тугай, Ю.І.; Ганус, О.І.; Старков, К.О. (Інститут електродинаміки НАН України, Київ, 2016)
Instrument transformers are sources of information required for mode control systems, power distribution networks, including advanced Smart Grid. Therefore, to ensure reliable operation of this source is relevant theoretical and practical task. The aim of this study is to develop a mathematical model of nonlinear dynamic analysis of electromagnetic transients in transformers and voltage rating switching surges in the distribution networks. It differs from previous studies in which the cause of failure of the voltage transformer ferroresonance considered quasi-stationary processes. The analyses of the equations are describing the electromagnetic transients in voltage transformer equivalent circuit. Using the resulting model makes it possible to anticipate the occurrence of surge and choose the measures their prevention. References 6, figure 1.